Effects of practising situational training on the transformation of motoric space junior basketball players - Korjenic, A.; Spahalic. E. (Sportski Logos, 2017)
For the purpose of improving young basketball players qualitat of playing and aim of gaining situational efficiency, behind basic fitness training, it is neccessary to practice and provide as many situational games (game with two baskets), because training methods are building up and developing specific situational elements of basketball game. The aim of this research is to determine the effects training model on the transformation of motoric space of young junior basketball players.